Perancangan Small Private Space pada Ruang Interior Perpustakaan Universitas Kristen Petra - Ferawati Chandra; Yusita Kusumarini; filipus priyo suprobo (Intra, 2014)
Flatpack furniture is disassembly furniture  and ready to be used with thin parts such as multiplex, scrap metal, cardboard, and so then packaged neatly and facilitate the delivery, this furniture was introduced in 1951 by Erie J. Sauder.In library room needed a private space especially for the readers, but it should be noted that library have a limited space.With efficient application of  Flatpack makes it easy to be included and be moved to the library room is quite limited.